ChemInform Abstract: Membrane Distillation Bioreactor (MDBR) ‐ A Lower Green‐House‐Gas (GHG) Option for Industrial Wastewater Reclamation. Issue 36 (September 2015) - Goh, Shuwen; Zhang, Jinsong; Liu, Yu; Fane, Anthony G.
Abstract Review: 132 refs.